ANALISIS STRUKTURAL OBJEKTIF DALAM NOVEL PESANTREN IMPIAN KARYA ASMA NADIA - Zumrotul Ilmiyah (EDU-KATA, 2021)
The research was conducted with the aim of (1) describing the objective structure aspects, (2) describing the value of moral education in the Asma Nadia Pesantren Impian novel. The object in this study is the aspect of objective structure and the value of moral education contained in the novel Pesantren Impian by Asma Nadia. The subject of his research was Asma Nadia's Dream Dream School. The instruments in this study were the researchers themselves, note books, ballpoint pens, and relevant books that could be used as reference material. Data collection techniques used by researchers used library techniques and note-taking techniques, namely by: (1) the researcher reads novel, (2) the author identifies the data, (3) records the results of the data relating to novel. The research method used by the researcher is the description method. The analysis technique used by researchers is the content technique of content analysis authors. The results of this study indicate that (1) the theme found in Asma Nadia's Pesantren Impian novel is the determination and effort of a woman to become a better person after undergoing a rehabilitation period in a pesantren. The main character is Girl, Rini is an additional figure, Teungku Umar, Teungku Hasan, Sinta and Santi. The background is divided into two types, namely the place setting and the time setting. The plot / groove used is a backlight or flash back. The point of view used is the third person's viewpoint of omniscience. (2) the value of moral education, namely respect, compassion and helpfulness.